Assessing stakeholders’ risk perceptions in a vulnerable coastal tourism destination (Faro beach, Southern Portugal) - Domingues, Rita B. (2020)
Effective coastal management is essential in regions where tourism is a main economic activity. However, poor communication and disagreement between stakeholders hamper the way decisions are conveyed to residents and home/business owners, potentially affecting economic development. We analysed managers and scientists' views regarding risk perceptions of Faro Beach (Algarve) residents, contributing to the identification of differences and similarities towards a sustainable management. We used a qualitative content analysis of managers and scientists' discourses. Managers and scientists recognize that residents, particularly fishermen, are quite knowledgeable about the risks they face by living at the beach. However, scientists and managers believe that residents easily forget about the problems due to an optimism bias and positive previous experience with hazards, that never caused fatalities or serious consequences, leading to an underestimation of the severity of the risks. Managers think that residents are not concerned about the environmental problems of Faro Beach, and both scientists and managers see education as the best solution to increase risk perception and concern of residents. We suggest that truly collaborative approaches to coastal management should be promoted, including an active involvement of residents in the decision process, thus increasing their self-efficacy and behavioural control.